Obama's energy policy: how far is it a transformative moment - Stanislaw, JA (Oxford Institute for Energy Studies, 2009)
In just six months, the Obama administration has made Washington the epicentre of a veritable revolution in American energy and environmental policy. After decades of lethargy, during which California and over thirty other states were the centre of innovation, hardly a week now passes without a landmark measure announced on the Hill or in the White House.